Synthesis, Structural and Optical Study of CdS Nanoparticles Doped with Different Concentration of Cu - Ankit Goyal; Vinay Sharma; Abhishek Sharma; Ravi Agarwal; K.B. Sharma; S.L. Kothari (Журнал нано- та електронної фізики)
Semiconductor nanoparticles have received much interest for their optical and electronic properties. CdS nanoparticles have been synthesized by chemical synthesis method using EDTA as a capping agent. Different concentration of Cu is doped in CdS nanoparticles during synthesis. X-ray diffraction (XRD) measurements showed that the nanoparticles have the structure of cubic phase. The broadening of XRD patterns indicates that the prepared samples are nanostructured. The optical absorption of the CdS nanoparticles is studied in the range of 200-800 nm. The optical properties of CdS nano particle were investigated by the UV-Vis absorption spectroscopy and Photoluminescence. The band gap of CdS nano particles has been determined.